Survei Sarana dan Prasarana Pendidikan Jasmani Olahraga dan Kesehatan Di MA Ar-Ridlo Kecamatan Pekuncen Kabupaten Banyumas Tahun Ajaran 2021/2022 - Irawan, Yogi Ferdy (Jurnal Kridatama Sains dan Teknologi, 2022)
Survey of sports and health physical education facilities and infrastructure in MA Ar-Ridlo, Pekuncen District, Banyumas Regency, 2021/2022 Academic Year. The formulation of the problem in this study is to find out exactly how many facilities and infrastructure there are in the MA Ar-ridlo school, Pekuncen District, Banyumas Regency. This research is motivated by a number of problems that exist at the MA Ar-Ridloschool, including that students often experience obstacles in carrying out practice, especially sports because of the very poor comparison between the availability of tools and the number of students. This study aims to explain and describe the situation naturally which is done by providing a systematic and accurate description of the situation or situation in the field, from the ongoing process the research aims to describe exactly the availability of physical education learning facilities and infrastructure through observation. The research method used in this study was interviews with physical education and sports teachers as subjects, totaling 2 people. The data analysis technique in this study is to compare the results of the study, in this case the amount of data on facilities and infrastructure with the regulatory standards set by the government ministry of education. This type of research is a qualitative descriptive type of research. According to Sugiyono (2013) if you look at the data, then data collection can use primary data sources and secondary data sources. Thus, the data of this research is descriptive. The data obtained include interview transcripts (interview results), field notes, photos, personal documents, and various other supporting data. Based on the results of data analysis and discussions that have been carried out by researchers, it can be concluded that the physical education facilities and infrastructure at MA Ar-Ridlo Kranggan, Pekuncen District, Banyumas Regency are not meeting the ideal standard because they are still constrained by the problem of the size of the area/place or land and the lack of financing to buy tools. Data on teaching aids facilities show that the availability of tools is less than 50 percent of the quota set by the government. This situation causes sports education facilities and infrastructure not to comply with the criteria set out in the government's ideal standards in education. The suggestion in this study, from researchers for the MA Ar-Ridlo school, is to immediately complete the facilities and infrastructure in accordance with government regulations, in this case the ministry of education, because with the achievement of school facilities and infrastructure standards that have been set by the government, learning will not experience obstacles and educational goals will be achieved. Keywords: Facilities and Infrastructure, Physical Education, Sports and Health